2009
DOI: 10.1002/glia.20871
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and neuropathic pain

Abstract: In contrast to physiological pain, pathological pain is not dependent on the presence of tissue-damaging stimuli. One type of pathological pain--neuropathic pain--is often a consequence of nerve injury or of diseases such as diabetes, AIDS, or cancer. Neuropathic pain can be agonizing, can persist over long periods, and, unfortunately, is often resistant to known painkillers. There is a rapidly growing body of evidence indicating that microglia, the CNS immune cells, have causal roles in the pathogenesis of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
197
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(207 citation statements)
references
References 130 publications
(183 reference statements)
7
197
1
2
Order By: Relevance
“…Our results provide evidence that P2X4R, while not P2X7R, expressed by microglia after chronic morphine treatment promote IL-1β release. But previous studies revealed that P2X7 receptor activation leads to the release of IL-1ß from microglia [33,39]. We think the main reason is due to a different microglia state.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our results provide evidence that P2X4R, while not P2X7R, expressed by microglia after chronic morphine treatment promote IL-1β release. But previous studies revealed that P2X7 receptor activation leads to the release of IL-1ß from microglia [33,39]. We think the main reason is due to a different microglia state.…”
Section: Discussionmentioning
confidence: 73%
“…Activated microglia adopt a phenotype characterized by increased expression of P2X4R and the P2X4R+ state are a central player in mechanisms for neuropathic pain which shares the same mechanisms as morphine-induced hyperalgesia [33]. Hyperalgesia induced by peripheral nerve injury does not occur in P2X4R-deficient mice [34].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence from studies of animal models of neuropathic pain indicates that neuropathic pain involves aberrant excitability of the nervous system [38][39][40]. There is evidence that changes occur in neurons as well as spinal microglia, the immune cells of the CNS [3,4,41].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that purines and their receptors are potential regulators of microglial function. It has also been reported that several purinoceptors are expressed in microglia, including P2X4, P2X7, P2Y6, and P2Y12 receptors [38]. Of these receptors, the P2X7 receptor is an ATP-gated ion channel, highly expressed in immune cells and microglia, where it modulates the release of inflammatory cytokines, such as IL-1β and IL-18 [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their role in maintaining CNS homeostasis, microglia play a central part in CNS pathologies [32][33][34], such as Alzheimer's disease, multiple sclerosis, and neuropathic pain. Therefore, our results may help to uncover potential targets for developing therapeutic treatments for neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%